Statistical Evaluation of Difluoro Triazole Acetophenone Photocatalysis Utilizing Ag-Fe Codoped TiO\(_2\) Nanoparticles - Darshana T. Bhatti; Sachin P. Parikh; Hitesh R. Ashani (Chemistry and Biochemistry: Research Progress Vol. 3, 2025)
Water pollution control and energy efficiency are thrust research areas nowadays. In this research, the performance of Ag-Fe codoped TiO2 (Ag-Fe CT) nanophotocatalyst for degradation of Diflouro Triazole Acetophenone (DTA) from aqueous solutions under solar and UV radiations were compared. The novel photocatalyst was synthesized using a sol-gel method with varying Ti to Ag mole ratio (10, 25,30, 40, 55). Synthetic wastewater was prepared from difluoro triazole acetophenone (DTA concentration 8 g/L and COD =75,000 mg/L). Ag-Fe CT 30 photocatalyst has shown maximum COD removal efficiency for solar and UV irradiation. The recyclability test proved that Ag-Fe CT 30 can be reused effectively three times without declining COD removal efficiency. Minitab software was used to study single and combined effects of pH, photocatalyst dose and Ti to Ag mole ratio parameters. A model showing the relation of parameters with COD reduction efficiency has been developed and optimization has been carried out for solar and UV photocatalysis. Results revealed that the optimal conditions for DTA removal were initial pH 5, photocatalyst dose of 3 g/L and Ti to Ag mole ratio of 30. Maximum COD removal efficiency of 76% and 86% were observed under solar and UV radiations, respectively. This study would be useful for the removal of non-biodegradable organics from high-strength COD effluent in an economical and eco-friendly way. In conclusion, the results of this study have proved that a response surface methodology is an important tool for studying statistics of results and predicting optimum conditions for solar and UV photocatalysis.